2017
DOI: 10.3354/dao03165
|View full text |Cite
|
Sign up to set email alerts
|

Experimental inoculation of oriental river prawn Macrobrachium nipponense with white spot syndrome virus (WSSV)

Abstract: The oriental river prawn Macrobrachium nipponense is an economically important species that is widely farmed in China. White spot syndrome virus (WSSV) is one of the most devastating pathogens of the cultured shrimp Litopenaeus vannamei, responsible for massive loss of its commercial products worldwide. We investigated the infectivity and pathogenicity of WSSV in adult M. nipponense using standardized conditions for L. vannamei. The median lethal dose of WSSV in adult M. nipponense was 103.84±0.06 copies g-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…WSSV is a member of genus Whispovirus, which belongs to the Nimaviridae family. WSSV can infect more than 93 species of shrimp and prawn [13], including Litopenaeus vannamei, Penaeus monodon, and M. japonicas [14]. The cumulative mortality of shrimp could approach 100% in 7-10 days after WSSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…WSSV is a member of genus Whispovirus, which belongs to the Nimaviridae family. WSSV can infect more than 93 species of shrimp and prawn [13], including Litopenaeus vannamei, Penaeus monodon, and M. japonicas [14]. The cumulative mortality of shrimp could approach 100% in 7-10 days after WSSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Further challenge studies showed M. rosenbergii could be infected by injection with WSSV stains Thai-1 and Viet, however, the infectious dose to reach 50% endpoint in M. rosenbergii needed 20-fold and 400-fold more than that in P. vannamei, respectively [22]. The half lethal dose (LD50) of WSSV to M. nipponense by injection was 10 (3.84±0.06) copies/g, which was about 1780-fold higher than that to P. vannamei at 10 (0.59±0.22) copies/g [23]. It was demonstrated that M. rosenbergii could clear injected infectious WSSV after 5 to 50 days post-injection [24].…”
Section: Discussionmentioning
confidence: 90%
“…All of the experimental materials and methods are referenced from Zhao et al (2017) [44]. The injection positions were between the third and fourth abdominal segments.…”
Section: Methodsmentioning
confidence: 99%